Ultrasound-assisted extraction of fructans from agave (Agave tequilana Weber var. azul) at different ultrasound powers and solid-liquid ratios - Sánchez Madrigal, Miguel Ángel; Amaya Guerra, Carlos Abel; Quintero Ramos, Armando; Báez González, Juan Gabriel; Núñez González, María Adriana; Ruiz Gutiérrez, Martha Graciela; Garzón Tiznado, José Antonio (2017)
Abstract The effects of ultrasound-assisted extraction (UAE) at different ultrasound power densities (UPDs; 40, 80, and 120 mW/mL) and solid:liquid (S:L) ratio (1:2, 1:3, and 1:6) on the extraction of carbohydrates from Agave tequilana plant of different ages were evaluated. Extracts obtained (6- and 7-year-old plant) were analyzed in the yield of carbohydrates (YC), fructan (FRU) content, simple sugars, fructan profile and the average degree of polymerization (DPn). UPD, S:L ratio, and plant age all affected YC, FRU, and DPn. Maximum YC and FRU were obtained from the older agave with UPD and S:L ratio of 120 mW/mL and 1:6, respectively; while glucose, fructose, and sucrose were highly released from the younger plant. Agave of 7-year-old presented the highest DPn. Fructan degradation occurred at high UPD, increasing the simple sugars and decreasing the DPn. Thermal-traditional extraction without sonication caused more fructan degradation; and overall, ultrasound enhanced fructan extraction and minimized fructan damage, representing a technological alternative for fructan extraction from agave. Keywords: agave; fructans; ultrasound; power density; solid:liquid ratio; plant age. Practical Application: Agave tequilana Weber var. azul plants have significant amounts of fructans. Extraction of these components by alternative methods such as ultrasound could represent advantages, improving the extraction and product quality. This research presents an alternative for the extraction of fructans assisted with ultrasound, evaluating different powers and solid-liquid ratios from agave heads of two different ages. Both variables, as well as age of agave showed a strong effect on fructan extraction. Ultrasound enhanced the extraction and minimized fructan damage, representing a technological alternative.